Uncovering spatial patterns in the natural and human history of Brazil nut (Bertholletia excelsa) across the Amazon Basin - Thomas, E.; Alcázar Caicedo, Carolina; McMichael, C.H.; Corvera, R.; Loo, J. (Wiley, 2015)
Our goal was to test the hypothesis that ancient humans substantially contributed to shaping the current distribution of Brazil nut (Bertholletia excelsa), an Amazonian tree species that has been important for human livelihoods since pre‐Columbian times. We scrutinized the putative association between Brazil nut and Amazonian Dark Earth soils (ADE) and geometric earthworks called geoglyphs, and examined the existence of continental patterns in human footprints on Brazil nut stands.Amazon Basin.We carried out a spatially explicit meta‐analysis of the variation of Brazil nut stand metrics across the Amazon Basin based on 87,617 density estimates and 488 average stand diameter assessments, and related these to previously published datasets and suitability maps of Brazil nut, ADE and geoglyphs.We found consistently higher Brazil nut suitability scores, stand densities and average stand diameters in the vicinities of ADE than at larger distances, regardless of their position along a gradient from south‐western to north‐eastern Amazonia. For geoglyph sites such a pattern was only found for Brazil nut habitat suitability scores. The available data further revealed an accumulation of Brazil nut stands with increasing densities and average diameters from south‐western to central and eastern Amazonia.Our findings suggest that the chance of encountering Brazil nut stands bearing the marks of past human influences increases from south‐western to central and eastern Amazonia. In south‐western Amazonia, the regeneration of Brazil nut seems to have been controlled predominantly by natural processes, whereas in central and eastern Amazonia, anthropogenic disturbance has been more important since pre‐Columbian times. However, it remains challenging to disentangle human influences on the distribution and abundance of Brazil nut from existing environmental gradients across the Amazon Basin. In general, the results of this meta‐analysis bode well for the future coexistence of Brazil nut with different forms of contemporary human land use.